Financial Statement Fraud Risk Factors and Auditor Response Strategies (gjstudies, 2025)
This research introduces a novel, multi-dimensional framework for assessing financial statement fraud risk that moves beyond traditional checklists and binary indicators.We propose that fraud risk exists on a dynamic continuum influenced by three interconnected domains: organizational narrative coherence, transactional ecosystem entropy,and digital behavioral residue. Traditional audit approaches often treat fraud risk factors as static and isolated, whereas our methodology recognizes the complex, adaptivenature of modern financial deception. We developed and tested a Continuous AnomalyResonance Detection (CARD) system that employs natural language processing to analyze management’s explanatory narratives alongside financial data, network theory tomap transactional ecosystems for entropy signals, and forensic analysis of digital audit trails for behavioral inconsistencies. Our longitudinal study of 47 publicly tradedcompanies over a three-year period revealed that narrative incoherence—discrepanciesbetween official explanations and quantitative patterns—predicted subsequent frauddetection with 78